Antimonial drugs entrapped into phosphatidylserine liposomes: physicochemical evaluation and antileishmanial activity - Samanta Etel Treiger Borborema; João Alberto Osso Junior; Heitor Franco de Andrade Junior; Nanci do Nascimento (Revista da Sociedade Brasileira de Medicina Tropical, 2016)
Abstract: INTRODUCTION: Leishmaniasis is a disease caused by the protozoan Leishmania that resides mainly in mononuclear phagocytic system tissues. Pentavalent antimonials are the main treatment option, although these drugs have toxic side effects and high resistance rates. A potentially alternative and more effective therapeutic strategy is to use liposomes as carriers of the antileishmanial agents. The aims of this study were to develop antimonial drugs entrapped into phosphatidylserine liposomes and to analyze their biological and physicochemical characteristics. METHODS: Liposomes containing meglumine antimoniate (MA) or pentavalent antimony salt (Sb) were obtained through filter extrusion (FEL) and characterized by transmission electron microscopy. Promastigotes of Leishmania infantum were incubated with the drugs and the viability was determined with a tetrazolium dye (MTT assay). The effects of these drugs against intracellular amastigotes were also evaluated by optical microscopy, and mammalian cytotoxicity was determined by an MTT assay. RESULTS: Liposomes had an average diameter of 162nm. MA-FEL showed inhibitory activity against intracellular L. infantum amastigotes, with a 50% inhibitory concentration (IC50) of 0.9μg/mL, whereas that of MA was 60μg/mL. Sb-FEL showed an IC50 value of 0.2μg/mL, whereas that of free Sb was 9μg/mL. MA-FEL and Sb-FEL had strong in vitro activity that was 63-fold and 39-fold more effective than their respective free drugs. MA-FEL tested at a ten-times higher concentration than Sb-FEL did not show cytotoxicity to mammalian cells, resulting in a higher selectivity index. CONCLUSIONS: Antimonial drug-containing liposomes are more effective against Leishmania-infected macrophages than the non-liposomal drugs.